ANALISIS YURIDIS TERHADAP DUGAAN TINDAK PIDANA KORUPSI SERTA TINDAK PIDANA ANCAMAN DAN KEKERASAN OLEH ISTERI KEPALA DESA - Dahwir, Ali (Faculty of Law, University of Palembang, 2025)
ABSTRACT This research discusses actions committed by the wife of the village head which are suspected of being criminal acts of corruption in the form of extortion and/or criminal acts of extortion and threats. The research method used is a normative research method using secondary data. Data were analyzed using qualitative methods. Based on the discussion, it was discovered that the actions carried out by NW could not be classified as criminal acts of corruption in the form of extortion because NW was not a civil servant or state official, which is one of the conditions for implementing article 12 letters e, f and g. The actions that NW has carried out are also not criminal acts of extortion and threats (Article 368 of the Criminal Code) because in carrying out these actions there were no elements of violence committed by NW, so NW's actions do not fulfill the elements of Article 368 of the Criminal Code. Keywords: Crime, Corruption, extortion and threats